Investigating the Implementation of Blended Learning in a Paragraph Writing Course in Promoting Student Engagement: The Case of Introductory Writing Course - Muhtia, Anggri; Suparno; Sumardi (Issues in Language Studies, 2018)
Blended learning, the instructional approach integrating online learning into face-to-face learning, is one of the approaches gaining widespread acceptance among educational practitioners. One of its advantages is to promote student engagement, which is viewed beneficial to ensure deep learning among students and address some educational issues. Although there is no specific formula for engaging all students into a course, blended learning is believed to enable student engagement further away than what is possible in a face-to-face instruction. This paper reports a case study conducted at a university in Indonesia. The purpose of the study was to investigate the implementation of blended learning in a paragraph writing course to promote student engagement. Data were collected through observations, interviews, and document analysis, and analysed using Miles, Huberman and Saldana’s (2014) interactive model. It was revealed that the instructional strategies in the course focused on the benefits of face-to-face learning as the main instructional method while the online learning was the supplementary to reinforce students’ knowledge and understanding. The implementation of blended learning in the course was able to promote student engagement particularly through the activities of uploading course materials, online writing assignments, online quizzes, student-teacher conferencing, class discussion, and group work.